Differentiation of Communicative Speech and Discourse State - Ramazon Radjabovich Bobokalonov (Research Parks Publishing LLC, 2022)
A language is a system of signs that includes words and syntax that have the meaning of words - this is a set of rules by which sentences are built. Speech is a language in practice. Speech is a specific type of human linguistic activity that provides communication between people and their socio-historical development. There are some differences between communicative speech and speech. Communicative speech competencies are based on mutual communication.